2003
DOI: 10.1021/bi034425k
|View full text |Cite
|
Sign up to set email alerts
|

Minor Groove Binding DNA Ligands with Expanded A/T Sequence Length Recognition, Selective Binding to Bent DNA Regions and Enhanced Fluorescent Properties

Abstract: DNA minor groove ligands provide a paradigm for double-stranded DNA recognition, where common structural motifs provide a crescent shape that matches the helix turn. Since minor groove ligands are useful in medicine, new ligands with improved binding properties based on the structural information about DNA-ligand complexes could be useful in developing new drugs. Here, two new synthetic analogues of AT specific Hoechst 33258 5-(4-methylpiperazin-1-yl)-2-[2'-(3,4-dimethoxyphenyl)-5'-benzimidazolyl] benzimidazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Amongst them, ligand 5-(4-methylpiperazin-1-yl)-2-[2 -(3,4-dimethoxyphenyl)-5 -benzimidazolyl]benzimidazole (DMA) displayed higher binding affinity to DNA and stabilised the altered DNA structure [9,10]. The cytotoxicity of the ligand was investigated on a glioma cell line (U-87) by studying its effects on cell survival and cell proliferation [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst them, ligand 5-(4-methylpiperazin-1-yl)-2-[2 -(3,4-dimethoxyphenyl)-5 -benzimidazolyl]benzimidazole (DMA) displayed higher binding affinity to DNA and stabilised the altered DNA structure [9,10]. The cytotoxicity of the ligand was investigated on a glioma cell line (U-87) by studying its effects on cell survival and cell proliferation [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] New applications are emerging from studies related to radiosensitization and radioprotection in relation to modification of radiation response by Hoechst derivatives. [17][18][19][20][21] Attempts have also been made to correlate these observations with different Hoechst analogues.…”
Section: Regular Articlementioning
confidence: 99%
“…55) This aspect is also demonstrated in femtosecond resolved fluorescence studies indicate the presence of weakly bound waters in the Hoechst 33258-DNA complex. 56,57) All these studies have indicated association of water in the Hoechst 33258-DNA complex.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9) Our group has also studied cellular responses of a few synthesized bisbenzimidazole derivatives in in-vitro systems. 10,11) Hoechst 33258 is a bisbenzimidazole molecule that binds strongly in the minor groove region of duplex DNA with predominant specificity for AT rich sequences. [12][13][14] Bisbenzimidazole compounds have also been reported to increase radiation induced cytotoxicity in several cancerous cell lines 15) and thus have an ability to improve radiotherapy.…”
mentioning
confidence: 99%